2020
DOI: 10.1111/jan.14452
|View full text |Cite
|
Sign up to set email alerts
|

Clustering clinical learning environment and mentoring perceptions of nursing and midwifery students: A cross‐sectional study

Abstract: Aims: This study aimed to explore nursing and midwifery students' evaluation of the clinical learning environment and mentoring and to identify distinct student profiles relating to their perceptions.Design: This study employed a cross-sectional design. Settings:The study population included nursing and midwifery students in a university hospital in Finland.Participants: All nursing and midwifery students who completed their clinical placement were invited to take part in the study in the academic year 2017-20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 53 publications
3
21
0
Order By: Relevance
“…A significant and positive correlation was found between every competence category and every CLES sub‐dimension, highlighting the strongest association between the Helping role and Pedagogical atmosphere on the ward and the Supervisory relationship. All in all, similar to earlier studies (Saarikoski et al, 2007; Saukkoriipi et al, 2020), in this study the supervisory relationship and a good mentor were found to be some of the main elements supporting students' competence development. Moreover, it seems that in the future, the mentors' role will be even greater as the role of teachers is decreasing as a result of diminishing resources in many countries (Immonen et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…A significant and positive correlation was found between every competence category and every CLES sub‐dimension, highlighting the strongest association between the Helping role and Pedagogical atmosphere on the ward and the Supervisory relationship. All in all, similar to earlier studies (Saarikoski et al, 2007; Saukkoriipi et al, 2020), in this study the supervisory relationship and a good mentor were found to be some of the main elements supporting students' competence development. Moreover, it seems that in the future, the mentors' role will be even greater as the role of teachers is decreasing as a result of diminishing resources in many countries (Immonen et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, private scheduled supervision sessions with the mentor during the practicum have been found meaningful (Immonen et al, 2019;Saukkoriipi et al, 2020); however, in this study, in some countries the students did not have any sessions of this kind, which might influence graduating nursing students' perceptions. In a clinical education ward, mentors discuss and reflect continuously with the students, helping them to find answers to problems related to patient care, which supports students' competence development (Manninen et al, 2015).…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations